Representaciones Sociales Sobre La Práctica De Fútbol De Salón Femenino En La Comunidad Educativa Jhon F. Kennedy (2019)
In the educational community of the institution Jhon F. Kennedy in the municipality of Calarcá (Quindío), where research was carried out on the social representations of the practice of women's club football, since formerly, the participation of women in the Indoor soccer sport has been minimal in reference to male participation, having as an investigative question what are the social representations about the practice of female indoor soccer in the Jhon F. Kennedy educational community ?. The methodology of qualitative approach and descriptive type was used with a work unit where the teachers, students and parents of this community were included, starting from their social, cultural and sports environment, taking into account their training areas and their own perspectives, through an application of a structured interview, to identify and know the perceptions that it brings, in turn to describe them, through the artisanal technique called savannah of colors. Consequently, there are some stereotypes and stigmas evidenced in these social representations, demonstrating that some people recognize that they are wrong, since they do not have valid arguments to affirm what they express, on the other hand, a part of society has been changing these subjective thoughts reflected culturally, which negatively affect this sport practice, affecting the image of women in their social and educational environment.